Shadow Prices in Public Program Evaluation Models - Azzi, Corry F.; Cox, James C. (Quarterly Journal of Economics, 1974)
Distributional implications of current models, 159. — Reformulation, 162. — Shadow pricing with budget constraints, 163. — Conclusion, 164.